2023
DOI: 10.1111/jvh.13798
|View full text |Cite
|
Sign up to set email alerts
|

Towards hepatitis C elimination in France: Scanvir, an effective model to test and treat drug users on dedicated days

Abstract: According to the French recommendations, the elimination of the hepatitis C virus by 2025 could be a realistic public health goal. Screening policies are being intensified, and access to treatment is promoted for patients who escape the usual care pathway.The 'Scanvir' program is an original strategy based on dedicated screening days, as part of the 'test, treat and cure HCV' event in addiction care centers in a French region, during which innovative screening technologies (RDTs, FibroScan® and pointof-care HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A recent meta-analysis found that the use of onsite POC RNA viral load had a positive impact on reduced turnaround times between HCV antibody testing and treatment initiation, and on testing and treatment uptake for PWID, especially when it was proposed at the same visit and on the same day [ 35 ]. In France, a recent study demonstrated the feasibility and acceptability of a ‘test and treat’ strategy based on dedicated screening days, proposing both HCV antibody and RNA testing in addiction care centers [ 36 ]. More generally, combining ‘test and treat’ strategies, linkage to care and early treatment initiation, would be a cost-effective option for reducing HCV incidence and improving PWID life expectancy in the French context [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis found that the use of onsite POC RNA viral load had a positive impact on reduced turnaround times between HCV antibody testing and treatment initiation, and on testing and treatment uptake for PWID, especially when it was proposed at the same visit and on the same day [ 35 ]. In France, a recent study demonstrated the feasibility and acceptability of a ‘test and treat’ strategy based on dedicated screening days, proposing both HCV antibody and RNA testing in addiction care centers [ 36 ]. More generally, combining ‘test and treat’ strategies, linkage to care and early treatment initiation, would be a cost-effective option for reducing HCV incidence and improving PWID life expectancy in the French context [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the identification of patients requiring treatment has become a challenging task that requires specific time-consuming interventions. In recent years, many interventions have been conducted in France with this goal, such as recontacting former patients not treated by DAAs and lost to follow-up by hepatology wards [32], or one-off screening interventions to enhance testing, linkage to care, and treatment initiations in the general population [33], at-risk populations [34,35], and in other countries [36]. In addition to screening and linkage to care, elimination efforts should also focus on infection and reinfection prevention measures.…”
Section: Discussionmentioning
confidence: 99%